Carbon Footprint Analysis of Motor Vehicles at the Military Academy - Darmoko; Agus Winarna; Suyono Thamrin (CV. AFDIFAL MAJU BERKAH, 2024)
The Military Academy, abbreviated as Akmil is the Central Implementing Agency at the Mabesad level in the field of education which is domiciled directly under the Kasad. Based on the organizational structure and duties (Orgas) Akmil consists of Leadership Elements, Leadership Assistant Elements, Service Elements, and Implementing Elements. Currently, Akmil personnel number 2,408 people with details of Officers 685, Non-Commissioned Officers 597, Tamtama 571, and Civil Servants 555 people. To facilitate access in service, Akmil provides official house facilities to each member in the Panca Arga Magelang Housing Complex. The majority of personnel who go to work in Akmil use motorized vehicles, both two-wheeled and four-wheeled. Round-trip activities from the Panca Arga Housing Complex to Akmil using motorized vehicles, of course, are inseparable from the so-called carbon footprint. The research method used is a review literature of several scientific articles related to exhaust emissions. The exhaust emissions in two-wheeled vehicles were 15,686.5 Kg/L, while four-wheeled vehicles were 9,155.8 Kg/L. It is necessary to calculate the emission of CO2 waste gases assuming the fuel used is pertalite and pertamax.